مسيرة التعايش الإنساني في التاريخ الحضاري: Human Coexistence and its Cultural and Historical Aspects - Hafiz Fazl Haq Haqqani (Al Manhal Research Journal, 2022)
The subject of human co-existence for the purpose of peace and non-violent communication is extremely important, even more today than in the past. The contention of this paper is that Semitic religions (Islam, Christianity and Judaism) have golden principles for coexistence and inter-faith harmony. However, this doctrine may be misunderstood in some societies due to the poor knowledge of religious teachings or wrong education. In this research, a descriptive and analytical method is used. This paper strongly recommends the need to have a true interpretation of religious teachings as well as a true approach to religious diversity to provide the culture of peace.